2014
DOI: 10.1002/2014jf003148
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐front variations and speed changes of calving glaciers in the Southern Patagonia Icefield from 1984 to 2011

Abstract: Patagonian icefields are losing volume, and their loss is due partly to rapid changes in their outlet glaciers that terminate in lakes or the ocean. Despite this key influence from outlet glaciers, relatively few of these calving glaciers have had high-frequency measurements on their frontal variations and ice speed changes. We describe here recent frontal variations and ice speed changes of all 28 major calving glaciers in the Southern Patagonia Icefield (SPI), including ice speed maps covering approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
121
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(140 citation statements)
references
References 52 publications
11
121
4
Order By: Relevance
“…The great depth of the Argentino Lake and the Upsala channel in particular might be related to the abundance of easily erodible rocks such as the slates of Pizarras Formation in the Upsala basin . This noticeable acceleration of glaciers at their terminus has been previously described for other outlet glaciers in Patagonia such as Jorge Montt Sakakibara and Sugiyama, 2014;Bown, 2015), where calving is driven at least in part by water depths near the front. Sakakibara and Sugiyama (2014) studied the glacier frontal variations of the outlet glaciers in the SPI.…”
Section: Surface Velocities Of Upsala Glaciermentioning
confidence: 71%
See 4 more Smart Citations
“…The great depth of the Argentino Lake and the Upsala channel in particular might be related to the abundance of easily erodible rocks such as the slates of Pizarras Formation in the Upsala basin . This noticeable acceleration of glaciers at their terminus has been previously described for other outlet glaciers in Patagonia such as Jorge Montt Sakakibara and Sugiyama, 2014;Bown, 2015), where calving is driven at least in part by water depths near the front. Sakakibara and Sugiyama (2014) studied the glacier frontal variations of the outlet glaciers in the SPI.…”
Section: Surface Velocities Of Upsala Glaciermentioning
confidence: 71%
“…This noticeable acceleration of glaciers at their terminus has been previously described for other outlet glaciers in Patagonia such as Jorge Montt Sakakibara and Sugiyama, 2014;Bown, 2015), where calving is driven at least in part by water depths near the front. Sakakibara and Sugiyama (2014) studied the glacier frontal variations of the outlet glaciers in the SPI. These authors reported a general recession trend for most glaciers in the area, though spatially and temporally varied.…”
Section: Surface Velocities Of Upsala Glaciermentioning
confidence: 71%
See 3 more Smart Citations